Efficacy of Ayurvedic Therapies in Treating Vicharchika: A Case Report on Holistic Skin Health Management - Dixit, Kusum; Moazzamipeiro, Fatemeh; Narine, Avvinish; Gupta, Nisha (International Research Journal of Ayurveda & Yoga, 2024)
This case study presents a 50-year-old female diagnosed with Vicharchika, an Ayurvedic skin disorder analogous to eczema, characterized by severe pruritus, extensive rashes, and serous discharge. What makes this case unique is the application of traditional Ayurvedic therapies—specifically Vamana ( emesis) and Virechana ( purgation)—to manage a chronic condition that had been resistant to allopathic treatments for over a decade. The patient experienced significant distress due to her symptoms, which included burning sensations and thickened, discoloured skin.The therapeutic intervention consisted of a comprehensive 38-day Ayurvedic regimen combining Shodhana ( purification) and Shamana ( palliative) therapies. Following a structured preparatory phase that included Deepana ( digestive enhancement) and Snehapana ( oleation), the patient underwent Vamana and Virechana. This was followed by supportive herbal medications and dietary modifications. The outcomes were remarkable; the patient reported substantial relief from itching, a notable reduction in skin lesions, and improved overall well-being, including enhanced sleep quality.The main takeaway from this case is the effectiveness of Ayurvedic treatment modalities in managing chronic skin disorders like Vicharchika. This case contributes to the scientific literature by demonstrating that integrative approaches combining traditional practices can offer significant relief and improve quality of life in patients where conventional treatments have failed. Further research is encouraged to explore the efficacy of such therapies in broader populations, underscoring the potential of Ayurveda in contemporary healthcare.